Study on Mechanical Properties of Gravelly Sand under Different Stress Paths - Dongjie Zhang; Fei Luo; Zhanyuan Zhu; Jiaming Liu; Jing Li; Bailin Li; Tianlang Xue (Advances in Civil Engineering)
To investigate the strength and deformation characteristics of gravelly sand on the Qinghai-Tibet Plateau under different stress paths, a series of triaxial shear tests was conducted under confining pressures of 50–400 kPa in four types of stress path conditions of conventional triaxial compression (CTC) (drained and undrained), triaxial compression (TC), and reduced triaxial compression (RTC). We can see from the test results that gravelly sand samples show strain hardening and shear contraction under the CTC (drained), TC, and RTC during the shearing process but exhibit strain softening under the CTC (undrained). To explore the microscopic deformation mechanism of gravelly sand, a characteristic angle θ was defined to reflect the relative movement of soil particles. The relationship between principal stress ratio σ1/σ3 and characteristic angle θ and that between void ratio e and characteristic angle θ were derived. Subsequently, the relationship expression of stress ratio η (q/p) and void ratio e was established, and the trend of void ratio e with the stress path was studied. To describe the strain hardening and strain softening characteristics of gravelly sand in different stress paths, a new dilatancy equation was obtained by introducing the characteristic state stress ratio Mc into the dilatancy equation of the modified Cam-Clay model based on the state-dependent dilatancy theory. Finally, an elastoplastic constitutive model of gravelly sand was established by applying a nonassociate flow rule. All model parameters can be determined by triaxial shear tests under different stress paths, and the comparison results show that the proposed model can well reflect the mechanical behaviors of gravelly sand under different stress paths.